The silver boat - Luanne Rice (New York . : Pamela Dorman Books/Viking, 2011)
Three far-flung sisters come home to Martha's Vineyard one last time. Their mother's beach house is the only place any of them ever found true happiness and they need to begin the difficult process of letting go. Memories of their grandmother, mother, and their Irish father, who sailed away the year Dar turned twelve, rise up and expose the fine cracks in their family myth--especially when a cache of old letters